Phantom Subspecies: The Wood Bison, Bison bison "athabascae" Rhoads 1897 Is Not a Valid Taxon, but an Ecotype - Geist, Valerius (ARCTIC, 1991)
The proposal that the "hybrid bison" of Wood Buffalo National Park (WBNP) be exterminated and replaced with "wood bison" has no taxonomic justification. The subspecies Bison bison athabascae Rhoads 1897 is based on the inadequate descriptions and taxonomically invalid criteria - i.e., body size and morphometrics. Its accepted pelage features are based on studies of the same herd of Nyarling River (NR) bison from Elk Island National Park (EINP). These pelage features, assumed to be genetically fixed, are ecotypic confinement effects, which NR bison share with EINP bull elk and moose. In bison the display hair acts analogous to deer antlers, which reflect their bearers' access to high-quality food during their growth. NR bison in captivity, in the Mackenzie Bison Sanctuary (MBS), and the original wood bison are "northern plains bison." Nor are WBNP bison distinguishable from MBS bison. A "wood bison" phenotype was also described as diagnostic for southern plains bison (B.b. bison Linnaeus 1958); the northern plains bison was named B.b. montanae Krumbiegel 1980. Consequently, B.b. athabascae = B.b. bison, as the latter has priority. Yet captive and introduced NR athabascae = montanae. Some WBNP bison resemble B. priscus, supporting the view that B. bison evolved as a hybrid between American and Siberian large-horned bison. Hybridization in large mammals need not be a tragedy for conservation.Key words: wood bison, plains bison, taxonomy, phenotype plasticity, ecotype, display organs, morphometry, subspecies, conservation Mots clés: bison des bois, bison des plaines, taxonomie, plasticité des phénotypes, écotype, organes de parade, morphométrie, sous-espèce, conservation